2017
DOI: 10.1186/s13023-017-0709-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary, bowel and sexual symptoms in a cohort of patients with Friedreich’s ataxia

Abstract: Background: Pelvic symptoms are distressing symptoms experienced by patients with Friedreich's Ataxia (FRDA). The aim of this study was to describe the prevalence of lower urinary tract symptoms (LUTS), bowel and sexual symptoms in FRDA. Methods: Questionnaire scores measuring LUTS, bowel and sexual symptoms were analysed with descriptive statistics as a cohort and as subgroups (Early/Late-onset and Early/Late-stage FRDA) They were also correlated with validated measures of disease severity including those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This demonstrates the importance of these measures to also investigate first abnormalities and that, again, underdiagnoses cannot be excluded, as data from the present study came from medical history rather than direct assessment. A recent study with a specific questionnaire to FRDA patients showed that up to 80% of patients reported lower urinary tract disorders, 64% bowel symptoms, and 83% sexual symptoms; here urinary dysfunctions were more frequent in late-onset FRDA patients and on those with longer disease duration (Lad et al, 2017). 49 We did not find other pathologies to be overrepresented in our FRDA cohort compared to estimates in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates the importance of these measures to also investigate first abnormalities and that, again, underdiagnoses cannot be excluded, as data from the present study came from medical history rather than direct assessment. A recent study with a specific questionnaire to FRDA patients showed that up to 80% of patients reported lower urinary tract disorders, 64% bowel symptoms, and 83% sexual symptoms; here urinary dysfunctions were more frequent in late-onset FRDA patients and on those with longer disease duration (Lad et al, 2017). 49 We did not find other pathologies to be overrepresented in our FRDA cohort compared to estimates in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with a specific questionnaire to FRDA patients showed that up to 80% of patients reported lower urinary tract disorders, 64% bowel symptoms, and 83% sexual symptoms; here urinary dysfunctions were more frequent in late-onset FRDA patients and on those with longer disease duration (Lad et al, 2017). 49 We did not find other pathologies to be overrepresented in our FRDA cohort compared to estimates in the general population. Of note, in a similar American cohort of 641 patients with FRDA, 10 patients (1.6%) had inflammatory bowel disease, a 3.5 times higher prevalence than in the general population, 50 but we could not confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic symptoms in FRDA have received little attention so far. Clinical studies in genetically confirmed populations reported a high prevalence of urinary symptoms and a recent report suggested that pelvic symptoms (urinary, sexual and lower gastrointestinal symptoms) tend to co-occur in FRDA [ 10 ]. Constipation was not systematically addressed, but in a report on FRDA associated with FXN exonic deletion, 3 out of 6 patients had a history of ileus [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we strengthened our findings by means of an extensive screening procedure and accurate patient characterization in a cohort of genetically confirmed FRDAs. Notably, in most of previous studies potential confounders such as vitamin deficiency or impaired glucose intolerance, which may per se cause an autonomic neuropathy, were not considered [ 10 , 11 , 27 ]. Moreover, the lack of validated scales precluded correlations with disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation